A sub-contratação nos serviços de manutenção: configuração da relação entre a grande empresa-cliente e as pequenas empresas fornecedoras - Mazzali, Leonel; Muñoz, Enrique Carlos Haro (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper identifies and analyzes the main variables which configurate the interaction process between thesmall maintenance service companies and the major customer company. After the literature review, thefollowing variables were selected: structure and policies of the customer company; procedures for identification,selection and evaluation of the suppliers; mechanisms of coordination, communication and supervision;technical knowledge degree, specialization and supplier agility; and the importance of the geographicalcloseness to the customer company. It is a descritive research, based on a survey carried out in 2005, throughAugust and November. The research used a structured questionnaire together with an intentional samplecomposed by 28 customer companies and by 16 small supplier companies who are located in São Paulo city.Despite the customer-supplier relationship is not characterized as a partnership, the research detected somechanges in the relationship, suggesting a closer perspective. Although the customer desires the specialization ofthe suppliers, the criteria applied to the selection and to the evaluation do not favor this profile. This researchis unique, on one side, due to the presence of a supply chain surrounding the supplier and, on the other, distinctvisions of the importance of the geographical closeness of the customer company, by the customer and supplier.Keyword: Maintenance, small business, partnership